Effects of vedolizumab in patients with primary sclerosing cholangitis and inflammatory bowel diseases - Lynch, K; Chapman, R; Keshav, S; Montano-Loza, A; Mason, A; Kremer, A; Vetter, M; De Krijger, M; Ponsioen, C; Trivedi, P; Hirschfield, G; Schramm, C; et al. (Elsevier, 2019)
Background & Aims Gut-homing lymphocytes that express the integrin α4β7 and CCR9 might contribute to development of primary sclerosing cholangitis (PSC). Vedolizumab, which blocks the integrin α4β7, is used to treat patients with inflammatory bowel diseases (IBD), but there are few data on its efficacy in patients with PSC. We investigated the effects of vedolizumab in a large international cohort of patients with PSC and IBD. Methods We collected data from European and North American centers participating in the International PSC Study Group from patients with PSC and IBD who received at least 3 doses of vedolizumab (n=102; median vedolizumab treatment duration, 412 days). Demographic and clinical data were collected from baseline and during the follow-up period (until liver transplantation, death, or 56 days after the final vedolizumab infusion). We analyzed overall changes in biochemical features of liver and proportions of patients with reductions in serum levels of alkaline phosphatase (ALP) of 20% or more, from baseline through last follow-up evaluation. Other endpoints included response of IBD to treatment (improved, unchanged, or worsened, judged by the treating clinician, as well as endoscopic score) and liver-related outcomes. Results In the entire cohort, the median serum level of ALP increased from 1.54-fold the upper limit of normal at baseline to 1.64-fold the upper limit of normal at the last follow-up examination (P=.018); serum levels of transaminases and bilirubin also increased by a small amount between baseline and the last follow-up examination. Serum levels of ALP decreased by 20% or more in 21 patients (20.6%); only the presence of cirrhosis (odds ratio, 4.48; P=.019) was independently associated with this outcome. Of patients with available endoscopic data, 56.8% had a response of IBD to treatment. Liver-related events occurred in 21 patients (20.6%), including bacterial cholangitis, cirrhosis decompensation, or transplantation. Conclusions In an analysis of patients with PSC and IBD in an international study group, we found no evidence for a biochemical response to vedolizumab, although serum level of ALP decreased by 20% or more in a subset of patients. Vedolizumab appears to be well tolerated and the overall response of IBD was the same as expected for patients without PSC.